Introduction to Latin America : twenty-first century challenges - Kirby, Peadar (Sage Publications, 2003)
Latin America in a Globalized World provides a completely new introduction to the political, social and economic forces shaping this essential region of undergraduate study today. It is the first textbook to place Latin America within a genuinely global context and introduce the debates and impact of globalization, neo-liberalism, democratization, and the environment.